Improving graduation rates: Legitimate practices and gaming strategies - Edwards, Noralee R.; Mindrila, Diana L. (Education Policy Analysis Archives, 2019)
Accountability pressures faced by teachers and leaders may lead well-intentioned educators to engage in strategic reporting and operational practices to increase test scores, graduation rates, and other indicators of student success. Such practices are referred to as gaming behaviors. School district personnel attending a Georgia educational conference (N=146) reported a significant prevalence of two such practices – purging data for students enrolled for a short period of time and fabricating withdrawal forms in case of audit. Exploratory factor analysis yielded three categories of strategies employed by school districts to improve reported graduation rates: a) practices that directly contradict the rules governing ethical reporting of data (Factor1); b) legitimate educational practices aiming to enhance student learning (Factor2); and c) possible gaming strategies aiming to exclude low performing students from the computation of graduation rates (Factor3). Latent profile analysis distinguished a) a group with average scores on all factors (N=120); and b) a group with significantly higher scores on Factor1 and Factor3 (N=26). The second group included a significantly larger proportion of individuals from districts with 5,000 – 10,000 students; districts of this size may have the expertise in-house to understand calculations and take strategic action with their data reporting practices.